Use of ionic liquids for [pi]-Conjugated polymer electrochemical devices - Lu, Wen; Fadeev, Andrei G; Qi, Baohua; Smela, Elisabeth (Science (American Association for the Advancement of Science), 2002)
Lu et al report results for electrochemical mechanical actuators, electrochromic windows, and numeric displays made from three types of pi-conjugated polymers. Experiments were performed under ambient conditions, yet the polymers showed negligible loss in electroactivity.